Agarwood Chromone Alleviates Gastric Ulcers by Inhibiting the NF-κB and Caspase Pathways Based on Network Pharmacology and Molecular Docking - Canhong Wang; Yulan Wu; Bao Gong; Junyu Mou; Xiaoling Cheng; Ling Zhang; Jianhe Wei (Pharmaceuticals)
Background: Agarwood has been widely used for the treatment of gastrointestinal diseases. Our research group has suggested that agarwood alcohol extracts (AAEs) provide good gastric mucosal protection. However, the exact mechanisms underlying this effect remain unclear. Objectives: This study aimed to investigate the ameliorative effect of agarwood chromone on gastric ulcers and its mechanism. Methods: Network pharmacology was used to predict the disease spectrum and key therapeutic targets of 2-(2-phenylethyl)chromone (CHR1) and 2-(2-(4-methoxyphenyI)ethyl)chromone (CHR2). Mice were orally administered CHR1 (20 and 40 mg/kg) and CHR2 (20 and 40 mg/kg) and the positive drug omeprazole as an enteric-coated capsule (OEC, 40 mg/kg) orally. After 7 days of pretreatment with the CHRs, gastric ulcers were induced using absolute ethanol (0.15 mL/10 g). The ulcer index, gastric histopathology, biochemical parameters, and inflammatory and apoptotic proteins were evaluated. Finally, binding of the core compounds to the key targets was verified via molecular docking and visualized. Results: The pharmacological results show that the CHRs reduced the gastric occurrence and ulcer inhibition rates by up to more than 70% in a dose-dependent manner. The CHRs decreased the levels of interleukin 6 (IL-6), interleukin 12 (IL-12), interleukin 18 (IL-18), and tumor necrosis factor α (TNF-α), and improved the severity of the pathological lesions in the gastric tissue. The expression of ATP-binding box transporter B1 (ABCB1), arachidonic acid-5-lipoxygenase (ALOX5), nuclear factor kappa B (NF-κB), cysteinyl aspartate specific proteinase 3 3 (Caspase3), and cysteinyl aspartate specific proteinase 9 (Caspase9) was inhibited, but the expression of B-cell lymphoma-2 (Bcl-2) was enhanced. The CHRs bound stably to the key targets via hydrogen bonding, van der Waals forces, etc. These results demonstrate that agarwood chromone compounds exert alleviative effects against the occurrence and development of gastric ulcers by inhibiting the NF-κB and caspase pathways. The CHRs have a therapeutic effect on gastric ulcers through anti-inflammation and anti-apoptosis mechanisms. Conclusions: This study suggests that agarwood may have a potential role in drug development and the prevention and treatment of gastrointestinal inflammation, and tumors.